Dosimetry Boron Neutron Capture Therapy in Liver Cancer with Sodium Boroncaptate as Boron Carrier using MCNP Calculation Software - Irhas, Irhas (2014)
ABSTRACT Boron Neutron Capture Therapy (BNCT) using physics principle when boron-10 irradiated by low energy neutron (thermal neutron). Boron and thermal neutron reaction produced alpha, lithium-7 particle and gamma ray. Irradiated time needed to ensure cancer dose enough. Liver cancer was primary malignant who located in liver (Hepatocellular carcinoma). Malignant in liver were different to metastatic from Breast, Colon Cancer, and the other. This condition was Metastatic Liver Cancer. Monte Carlo method used by Monte Carlo N-Particle (MCNP) Software. Probabilistic approach used for probability of interaction occurred and record refer to characteristic of particle and material. In this case, thermal neutron produced by model of Collimated Thermal Column Kartini Research Nuclear Reactor, Yogyakarta. Sodium boroncaptate (BSH) was used as in this research. BSH had effected in liver for radiation quality factor as 0.8 in health tissue and 2.5 in cancer tissue. Modelling organ and source used liver organ who contain of cancer tissue and research reactor. Variation of boron concentration was 20, 25, 30, 35, 40, 45, and 47 μg/g cancer. Output of MCNP calculation were neutron scattering dose, gamma ray dose and neutron flux from reactor. Neutron flux used to calculate alpha, proton and gamma ray dose from interaction of tissue material and thermal neutron. Variation of boron concentration result dose rate to every variation were0,042; 0,050; 0,058; 0,067; 0,074; 0,082; 0,085 Gy/sec. Irradiation time who need to every concentration were 1194,687 sec (19 min 54 sec);999,645 sec (16 min 39 sec); 858,746 sec (14 min 19 sec); 743,810 sec (12 min 24 sec); 675,156 sec (11 min 15 sec); 608,480 sec (10 min 8 sec); 585,807sec (9 min 45 sec). Irradiating time could shortly when boron concentration more high.